An observational study on clinico-hormonal profile of adult onset acne in females - Mohankar, Atul D.; Biswal, Saumita G.; Sinha, Mayank; Verma, Nisha M.; Rafat, Kashifa (International Journal of Research in Dermatology, 2024)
Background: Acne is a common chronic inflammatory dermatological disorder of pilosebaceous unit in adolescents, but surprisingly its incidence is increasing in adults. Adult onset acne is quite common in females and there is paucity of data on its clinico-hormonal profile. Our objective was to evaluate and study the clinic-hormonal profile in adult onset acne in females. Methods: Patients over the age of 25 years were included in the study. A detailed history and examination along with hormonal investigations were done for each patient. Results: Out of 24,266 outdoor patients attending Dermatology OPD during 5 months, 180 female patients with adult onset acne were included in the study and prevalence of Adult acne was 0.74%. The mean age was found to be 31.61 years. Majority of the patients had grade II acne (68.33%). Premenstrual flare was seen in 50% (90) patients, 21.11% (38) patients had dysmenorrhea, Hirsutism was seen in 30% (54) patients. Levels of total serum testosterone was markedly increased in 3 (1.66%) patients while serum prolactin in 2(1.1%) patients. Thyroid abnormalities were seen in (12.77%) 23 cases. LH:FSH ratio was deranged in 37 (20.56%) patients. The fasting Insulin level was increased in 4 (2.22%%) patients, Ultrasound of pelvis revealed 59 (32.77%) patients had polycystic ovaries. Conclusions: Adult female acne is a complex multifactorial condition, different from teenage acne. Various hormonal imbalances can present as adult acne. So various endocrinological investigations to be carried out in adult onset female acne.